2017
DOI: 10.1111/obr.12531
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of genetic syndromes with obesity

Abstract: Syndromic monogenic obesity typically follows Mendelian patterns of inheritance and involves the co-presentation of other characteristics, such as mental retardation, dysmorphic features and organ-specific abnormalities. Previous reviews on obesity have reported 20 to 30 syndromes but no systematic review has yet been conducted on syndromic obesity. We searched seven databases using terms such as 'obesity', 'syndrome' and 'gene' to conduct a systematic review of literature on syndromic obesity. Our literature … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
133
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 156 publications
(135 citation statements)
references
References 250 publications
(167 reference statements)
1
133
0
1
Order By: Relevance
“…Heritability estimates of obesity from twin and family studies range from 0.25 to 0.90 , suggesting a large portion of obesity risk may be because of inherited factors. To date, genetic association studies have identified 63, 12 and 157 loci involved in monogenic syndromic, monogenic non‐syndromic and polygenic forms of obesity, respectively .…”
Section: Introductionmentioning
confidence: 99%
“…Heritability estimates of obesity from twin and family studies range from 0.25 to 0.90 , suggesting a large portion of obesity risk may be because of inherited factors. To date, genetic association studies have identified 63, 12 and 157 loci involved in monogenic syndromic, monogenic non‐syndromic and polygenic forms of obesity, respectively .…”
Section: Introductionmentioning
confidence: 99%
“…Heritability estimates for BED and obesity range from 41% to 57% and from 25% to 90% . Multiple genes responsible for monogenic syndromic and non‐syndromic, oligogenic and polygenic forms of obesity have been identified . However, it is unclear as to which genes may predispose individuals to BED .…”
Section: Introductionmentioning
confidence: 99%
“…These all have variable effects on body fat mass. Of the 79 forms of identified obesity syndromes, 19 have been fully elucidated, 11 have been partially elucidated, while 27 have been mapped to a chromosomal region but not characterized . Monogenic obesity presents as a rare condition, with severe obesity being attributable to recessive mutations coding for key metabolites in pathways for the hypothalamic control of appetite.…”
Section: Genetics Of Obesitymentioning
confidence: 99%
“…Of the 79 forms of identified obesity syndromes, 19 have been fully elucidated, 11 have been partially elucidated, while 27 have been mapped to a chromosomal region but not characterized. 14…”
Section: Genetics Of Obesitymentioning
confidence: 99%